The Electoral Value of Constituency-Oriented Parliamentary Questions in Hungary and Romania. Issue 4 (31st January 2018) - Chiru, Mihail
Abstract: Drawing on a unique data set that combines legislative behaviour data and electoral results at two elections in Romania (2008, 2012) and one in Hungary (2014), the study assesses the overall electoral value of parliamentary questions dealing with local issues. Our multivariate regression analyses illustrate that the effect of constituency questions is distinguishable from that of the overall parliamentary effort of the MPs. Constituency questions brought Romanian MPs significantly more votes at each of the last two elections. In Hungary, where the scope for a personal vote was much more limited at the analysed elections, no effect is found.